Study on Ultrasonically-Enhanced Sulfuric Acid Leaching of Nickel from Nickel-Containing Residue - Zhanyong Guo (Crystals, 2021)
In this paper, nickel-containing residue, a typical solid waste produced in the battery production process, was used to study the cavitation characteristics of ultrasonic waves in a liquid–solid reaction. The ultrasonically-enhanced leaching technology for multicomponent and complex nickel-containing residue was studied through systematic ultrasonic-conventional comparative experiments. An ultrasonic leaching kinetics model was established which provided reliable technological guidance and basic theory for the comprehensive utilization of nickel-containing residue. In the study, it was found that ultrasonically-enhanced leaching for 40 min obtained the same result as conventional leaching for 80 min, and the Ni extraction degree reached more than 95%. According to the kinetic fitting of the leaching process, it was found that the sulfuric acid leaching process belonged to the diffusion-controlled model of solid product layers under conventional and ultrasonic conditions, and the activation energy of the reaction was Ea1 = 17.74 kJ/mol and Ea2 = 5.04 kJ/mol, respectively.